Letter from James B. Guthrie to James Curtis Booth, August 7, 1854 - Guthrie, James (1854)
James B. Guthrie (1792 - 1869), United States Secretary of the Treasury from 1853-1857, writes to James Curtis Booth (1810-1888) concerning Booth's authorization to proceed with fusible alloy work.
Keywords: Guthrie, James, 1792-1869; Booth, James Curtis, 1810-1888; United States. Department of the Treasury; United States Mint; Mint of the United States